Inhibitors of Stimulator of Interferon Genes from 2019 to July 2022: An Overview of the Structure and Bioactivity - Xu, Feng; Tian, Xinjian; Zhu, Qiangsheng; Feng, Ziwen; Li, Hui; Dai, Wei; Zhou, Yeling; You, Qi-Dong; Xu, Xiaoli (Current Drug Targets, 2023)
Stimulator of interferon genes (STING) plays a vital role in the human innate immune system. Aberrant expression of STING has been proven to be associated with several diseases, such as STING-associated vasculopathy with onset in infancy, Aicardi-Goutieres syndrome, and systemic lupus erythematosus. Therefore, inhibition of the STING signaling pathway can also be expected to provide effective therapeutic strategies for treating specific inflammatory and autoimmune diseases. However, the development of STING inhibitors is still in its infancy. There is still a need for additional efforts toward the discovery of new skeletons and more potent lead compounds for STING inhibition to meet clinical demand. In this review, we provide a summary of STING inhibitors, classified by different structural skeletons, reported in patents published from 2019 to July 2022. In addition, we also focus on the STING inhibitors, representative structures, biological activity, and mechanisms of action.
Keywords: inhibitors